2008
DOI: 10.1063/1.3025826
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic study on rotational and vibrational temperature of N2 and N2+ in dual-frequency capacitively coupled plasma

Abstract: By using optical emission spectroscopy, the vibrational and rotational temperatures of N2 and N2+ in capacitively coupled plasma (CCP) discharges driven by dual-frequency 41MHz and 2MHz are investigated. The vibrational and rotational temperatures are measured based on the N2+ first negative system and N2 second positive system overlapped molecular emission optical spectrum, using the method of comparing the measured and calculated spectra with a least-square procedure. The influence of the rotational and vibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 42 publications
2
35
0
Order By: Relevance
“…However, the rotational temperature of 1NS is higher than those of 1PS and 2PS, and consequently, it does not correspond to the translational temperature of neutral molecules. Similar results are reported on T R of 1NS of low-pressure discharge nitrogen plasmas (Huang et al, 2008). These experimental results possibly indicate that the dominant population process of excited states B 2 Σ u + of N 2 + is not the direct excitation from the ground state of neutral N 2 molecule, and not from excited states of neutral molecular state, either.…”
Section: Progresses Insupporting
confidence: 77%
See 1 more Smart Citation
“…However, the rotational temperature of 1NS is higher than those of 1PS and 2PS, and consequently, it does not correspond to the translational temperature of neutral molecules. Similar results are reported on T R of 1NS of low-pressure discharge nitrogen plasmas (Huang et al, 2008). These experimental results possibly indicate that the dominant population process of excited states B 2 Σ u + of N 2 + is not the direct excitation from the ground state of neutral N 2 molecule, and not from excited states of neutral molecular state, either.…”
Section: Progresses Insupporting
confidence: 77%
“…As for nitrogen ions, a number of papers reported that the first negative system (1NS), originated from B 2  u + state of N 2 + ion, shows higher rotational temperature than that from neutral molecules (e.g., Huang et al, 2008).…”
mentioning
confidence: 99%
“…Simulated spectra are iteratively fitted to the experimental data to extract both vibrational temperature (T v ) and rotational temperature(T r ) using the same method as previously fully outlined in Greig et al [6]. At pressures of a few Torr, the collision frequency is sufficiently high to assume that the rotational and translational temperatures are in thermal equilibrium [15][16][17].…”
Section: Rovibrational Spectroscopy Methodsmentioning
confidence: 99%
“…18 The N þ 2 first negative system has been used to find gas temperature in a gliding arc discharge at atmospheric pressure, 13 a pulsed DC hollow cathode discharge, 19 and a low pressure dual frequency CCP. 20 The N 2 second positive system (C 3 P u ! B 3 P g ) is the most common band used, with gas temperature estimates made for capacitively coupled and inductively coupled plasma discharges, 5,10,[20][21][22] a radio-frequency (RF) helicon discharge, 23 and low pressure glow or positive column discharges.…”
Section: Introductionmentioning
confidence: 99%
“…20 The N 2 second positive system (C 3 P u ! B 3 P g ) is the most common band used, with gas temperature estimates made for capacitively coupled and inductively coupled plasma discharges, 5,10,[20][21][22] a radio-frequency (RF) helicon discharge, 23 and low pressure glow or positive column discharges. 24,25 Temperatures of higher pressure and atmospheric pressure discharges have also been analysed with the N 2 second positive system, 4,26,27 and also temperatures during the first 400 ns of spark breakdown for an N 2 discharge.…”
Section: Introductionmentioning
confidence: 99%